Systematic screening and assessment of psychosocial well-being and care needs of people with cancer - Schouten, Bojoura; Avau, Bert; Bekkering, Geertruida Trudy E; Vankrunkelsven, Patrick; Mebis, Jeroen; Hellings, Johan; Van Hecke, Ann (Cochrane database of systematic reviews, 2019)
Receiving a diagnosis of cancer and the subsequent related treatments can have a significant impact on an individual's physical and psychosocial well-being. To ensure that cancer care addresses all aspects of well-being, systematic screening for distress and supportive care needs is recommended. Appropriate screening could help support the integration of psychosocial approaches in daily routines in order to achieve holistic cancer care and ensure that the specific care needs of people with cancer are met and that the organisation of such care is optimised. To examine the effectiveness and safety of screening of psychosocial well-being and care needs of people with cancer. To explore the intervention characteristics that contribute to the effectiveness of these screening interventions. We searched five electronic databases in January 2018: the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, Embase, PsycINFO, and CINAHL. We also searched five trial registers and screened the contents of relevant journals, citations, and references to find published and unpublished trials. We included randomised controlled trials (RCTs) and non-randomised controlled trials (NRCTs) that studied the effect of screening interventions addressing the psychosocial well-being and care needs of people with cancer compared to usual care. These screening interventions could involve self-reporting of people with a patient-reported outcome measures (PROMs) or a semi-structured interview with a screening interventionist, and comprise a solitary screening intervention or screening with guided actions. We excluded studies that evaluated screening integrated as an element in more complex interventions (e.g. therapy, coaching, full care pathways, or care programmes). Two review authors independently extracted the data and assessed methodological quality for each included study using the Cochrane tool for RCTs and the Risk Of Bias In Non-randomised Studies - of Interventions (ROBINS-I) tool for NRCTs. Due to the high level of heterogeneity in the included studies, only three were included in meta-analysis. Results of the remaining 23 studies were analysed narratively. We included 26 studies (18 RCTs and 8 NRCTs) with sample sizes of 41 to 1012 participants, involving a total of 7654 adults with cancer. Two studies included only men or women; all other studies included both sexes. For most studies people with breast, lung, head and neck, colorectal, prostate cancer, or several of these diagnoses were included; some studies included people with a broader range of cancer diagnosis. Ten studies focused on a solitary screening intervention, while the remaining 16 studies evaluated a screening intervention combined with guided actions. A broad range of intervention instruments was used, and were described by study authors as a screening of health-related quality of life (HRQoL), distress screening, needs assessment, or assessment of biopsychosocial symptoms or overall well-being. In 13 studies, the screening was a self-reported questionnaire, while in the remaining 13 studies an interventionist conducted the screening by interview or paper-pencil assessment. The interventional screenings in the studies were applied 1 to 12 times, without follow-up or from 4 weeks to 18 months after the first interventional screening. We assessed risk of bias as high for eight RCTs, low for five RCTs, and unclear for the five remaining RCTs. There were further concerns about the NRCTs (1 = critical risk study; 6 = serious risk studies; 1 = risk unclear).Due to considerable heterogeneity in several intervention and study characteristics, we have reported the results narratively for the majority of the evidence.In the narrative synthesis of all included studies, we found very low-certainty evidence for the effect of screening on HRQoL (20 studies). Of these studies, eight found beneficial effects of screening for several subdomains of HRQoL, and 10 found no effects of screening. One study found adverse effects, and the last study did not report quantitative results. We found very low-certainty evidence for the effect of screening on distress (16 studies). Of these studies, two found beneficial effects of screening, and 14 found no effects of screening. We judged the overall certainty of the evidence for the effect of screening on HRQoL to be very low. We found very low-certainty evidence for the effect of screening on care needs (seven studies). Of these studies, three found beneficial effects of screening for several subdomains of care needs, and two found no effects of screening. One study found adverse effects, and the last study did not report quantitative results. We judged the overall level of evidence for the effect of screening on HRQoL to be very low. None of the studies specifically evaluated or reported adverse effects of screening. However, three studies reported unfavourable effects of screening, including lower QoL, more unmet needs, and lower satisfaction.Three studies could be included in a meta-analysis. The meta-analysis revealed no beneficial effect of the screening intervention on people with cancer HRQoL (mean difference (MD) 1.65, 95% confidence interval (CI) -4.83 to 8.12, 2 RCTs, 6 months follow-up); distress (MD 0.0, 95% CI -0.36 to 0.36, 1 RCT, 3 months follow-up); or care needs (MD 2.32, 95% CI -7.49 to 12.14, 2 RCTs, 3 months follow-up). However, these studies all evaluated one specific screening intervention (CONNECT) in people with colorectal cancer.In the studies where some effects could be identified, no recurring relationships were found between intervention characteristics and the effectiveness of screening interventions. We found low-certainty evidence that does not support the effectiveness of screening of psychosocial well-being and care needs in people with cancer. Studies were heterogeneous in population, intervention, and outcome assessment.The results of this review suggest a need for more uniformity in outcomes and reporting; for the use of intervention description guidelines; for further improvement of methodological certainty in studies and for combining subjective patient-reported outcomes with objective outcomes.